2008
DOI: 10.1172/jci34871
|View full text |Cite
|
Sign up to set email alerts
|

Apelin signaling antagonizes Ang II effects in mouse models of atherosclerosis

Abstract: Apelin and its cognate G protein-coupled receptor APJ constitute a signaling pathway with a positive inotropic effect on cardiac function and a vasodepressor function in the systemic circulation. The apelin-APJ pathway appears to have opposing physiological roles to the renin-angiotensin system. Here we investigated whether the apelin-APJ pathway can directly antagonize vascular disease-related Ang II actions. In ApoE-KO mice, exogenous Ang II induced atherosclerosis and abdominal aortic aneurysm formation; we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
272
6
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 221 publications
(299 citation statements)
references
References 55 publications
17
272
6
4
Order By: Relevance
“…Whether APJ multimeric species observed in the fetal and adult pulmonary tissues in our study correspond to homo-or hetero-multiples of the receptor is still not known and could only be clarified by further studies. Nonetheless, it was already demonstrated in vitro that APJ can form heterodimers with angiotensin II AT1 receptor [7]. Moreover immunohistochemical studies performed in our lab revealed that all renin-angiotensin system components, including AT1 and .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Whether APJ multimeric species observed in the fetal and adult pulmonary tissues in our study correspond to homo-or hetero-multiples of the receptor is still not known and could only be clarified by further studies. Nonetheless, it was already demonstrated in vitro that APJ can form heterodimers with angiotensin II AT1 receptor [7]. Moreover immunohistochemical studies performed in our lab revealed that all renin-angiotensin system components, including AT1 and .…”
Section: Discussionmentioning
confidence: 77%
“…Currently the relation between these two systems is described to be a direct interaction of the two systems at both molecular and transcriptional levels to mediate opposing physiological actions [2]. APJ and AT1 receptor-receptor interactions are presently accounted as the potential molecular mechanism of crosstalk responsible for this reciprocal counter-regulation between apelin and Ang II pathways, since it was observed in vitro that the respective receptors can form heterodimers and that this heterodimerisation influences downstream signaling [7]. Our observations on fetal lung growth are in accordance with others reporting that the proposed effects of the apelin-APJ system are opposite to those of the Ang II-AT1 receptor pathway [7,44].…”
Section: Discussionmentioning
confidence: 99%
“…Levels of ROS1 phosphorylation were higher in Gpx1 -/-Apoe -/-mice (P < 0.05) without differences in ROS1 protein. in basal medium (SmBM) for 72 hours, according to conventional protocols (45). In vitro ROS1 inhibition studies were completed by adding 40 μM genistein to the cell-culture media.…”
Section: Methodsmentioning
confidence: 99%
“…Human coronary artery SMCs (HCASMCs) and aorta/stented vessel lysates (n ≥ 5 per group) were used for immunoprecipitation and immunoblotting performed using a previously described method (45).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation